Immediate Reactions to Fluorescein and Indocyanine Green in Retinal Angiography: Review of Literature and Proposal for Patient’s Evaluation - Meira J (Dove Medical Press, 2020)
Jorge Meira, 1,* Maria Luís Marques, 2,* Fernando Falcão-Reis, 1, 3 Eva Rebelo Gomes, 2 Ângela Carneiro 1, 3 1Department of Ophthalmology, Centro Hospitalar Universitário São João, Porto, Portugal; 2Department of Allergy and Clinical Immunology, Centro Hospitalar Universitário do Porto, Porto, Portugal; 3Department of Surgery and Physiology, Faculty of Medicine, University of Porto, Porto, Portugal*These authors contributed equally to this workCorrespondence: Jorge MeiraDepartment of Ophthalmology of São João Hospital, Avenida Prof. Hernâni Monteiro, Porto 4202 – 451, PortugalTel +351225512100Fax +351225513669Email jorgesmeira@gmail.comIntroduction: Contrast rapid sequence angiography with fluorescein or indocyanine green (ICG) is a diagnostic procedure commonly used in ophthalmology. Adverse reactions to fluorescein and ICG are rare and may be classified as toxic, of hypersensitivity and non-specific. The evaluation and management of a patient with an adverse reaction is a challenge for the majority of ophthalmologists, as is the assessment of risk factors that may contraindicate the procedure.Purpose: We aim to review the concepts underlying adverse reactions to fluorescein and ICG, especially those of hypersensitivity, and present a proposal or the evaluation of the patients in need to perform retinal angiography and for the treatment of immediate reactions to fluorescein and ICG.Methods: The available literature was examined using PubMed-Medline, and using the MeSH terms “fluorescein”, “Indocyanine green”, “ophthalmic dyes”, “retinal angiography”, “adverse reactions”, and “allergic reaction”.Conclusion: This review may help ophthalmologists to identify patients with higher risk of a hypersensitivity reaction and give them tools to recognize patients with suspected hypersensitivity that may benefit from an allergy study.Keywords: fluorescein, indocyanine green, ophthalmic dyes, retinal angiography, adverse reactions, hypersensitivity reaction